40 USM EXPERTS READY TO ASSIST IN IMPROVING ENGLISH LANGUAGE PROFICIENCY - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 23 July 2015 – Universiti Sains Malaysia (USM) has approximately 40 educators with the expertise in the English language and who are ready to contribute to the nation.